Improving optical and electrical performances of aluminum-doped zinc oxide thin films with laser-etched grating structures. Issue 6 (15th March 2021) - Huang, Li-jing; Zhao, Lei; Li, Bao-jia; Zhang, Yao; Wang, Yi-lun; Wang, Yong-ying; Ren, Nai-fei; Song, Juan
Abstract: A laser etching method was performed to achieve the dual purpose of fabricating grating structures and laser annealing on aluminum-doped zinc oxide (AZO) thin films, and thus improve the film photoelectric performances. Different line spacings and laser fluences were adopted to systematically explore the optimal laser etching condition. Too narrow line spacings or too high laser fluences led to light reflections at the grating external surface to cause more light dissipation, and too wide line spacings or too low laser fluences resulted in relatively small total grating lateral areas being detrimental to multiple internal light reflections. Moreover, too narrow line spacings brought about laser-caused lattice disorder and too high laser fluences produced laser-ablated spots or overburned traces. Therefore, using the medium line spacing and laser fluence, e.g. 40 μm and 0.6 J/cm 2 in the present work, was more suitable for synchronously realizing grating structure fabrication and laser annealing. The corresponding AZO film exhibited the maximum figure of merit of 2.89 × 10 −2  Ω −1, which was 1.6 times that of the untreated AZO film. This study is expected to expand performance improvement methods of TCO films and promote the application of laser-etched grating structures.